THE ROLE OF INDEPENDENT PHYSICAL EXERCISES IN THE FORMATION OF A HEALTHY LIFESTYLE FOR STUDENTS - T.V. Andrianov (Academy of Cognitive and Natural Sciences, 2008)
Hearty life style formation of student youth has to de put into effect according current training method to self-dependant physical training lessons.